Do IgM antibodies protect against atherosclerosis in SLE? - McMahon, Maureen (Nat Rev Rheumatol, 2016)
Autoantibodies against end products of lipid peroxidation have unexpected effects on atherosclerosis in systemic lupus erythematosus (SLE). The discovery of their effects could lead to new theories about the role of the adaptive immune system in SLE.